Oral manifestations of COVID-19: integrative literature review (Research, Society and Development, 2022)
Introduction: Oral lesions have been reported in patients with COVID-19 with changes in the oral mucosa, including effects of concomitant infections. Among the concomitant infections considered worth mentioning are: Herpes, Candidosis and Mucormycosis. Objective: The objective of this study was to c the oral manifestations in adults who had COVID-19. Methods: An integrative literature review was carried out, searching the PUBMED, SCIELO, PERIODICOS CAPES and LILACS/BVS/BIREME databases with the following search keywords: “oral manifestation”, “mucosal lesions”, “covid-19”, “adults” and “periodontal” associated using the Boolean operator “and”. Results: After applying the eligibility criteria listed by the PRISMA-ScR strategy, 21 articles were selected to answer the question: “What are the most common oral and periodontal manifestations in adults who have had COVID-19?”. Conclusion: It is noticed that COVID-19 and its oral manifestations have been reported and related, but more studies are needed to clarify and make this relationship clearer.